2013
DOI: 10.1136/bmj.f4822
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of intravenous iron therapy in reducing requirement for allogeneic blood transfusion: systematic review and meta-analysis of randomised clinical trials

Abstract: Objectives To evaluate the efficacy and safety of intravenous iron, focusing primarily on its effects on haemoglobin, requirement for transfusion, and risk of infection.Design Systematic review and meta-analysis of randomised controlled trials investigating the safety and efficacy of intravenous iron therapy. Eligibility criteria for selecting studies Eligible trials were randomised controlled trials of intravenous iron compared with either no iron or oral iron. Crossover and observational studies were exclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
237
3
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(258 citation statements)
references
References 94 publications
8
237
3
10
Order By: Relevance
“…Thus, it is not unexpected that hemoglobin response is better to intravenous than to oral iron, as documented in several studies. 36 One drawback of intravenous iron has been the need for multiple infusions. However, some preparations on the market may replace the total dose needed to correct iron deficiency anemia (up to 1000 mg) in a single or a couple of infusions (Table 4).…”
Section: Intravenous Iron: Indications and Controversiesmentioning
confidence: 99%
“…Thus, it is not unexpected that hemoglobin response is better to intravenous than to oral iron, as documented in several studies. 36 One drawback of intravenous iron has been the need for multiple infusions. However, some preparations on the market may replace the total dose needed to correct iron deficiency anemia (up to 1000 mg) in a single or a couple of infusions (Table 4).…”
Section: Intravenous Iron: Indications and Controversiesmentioning
confidence: 99%
“…A review of 75 studies (42 of them investigated IS) included a meta-analysis of 24 studies (n = 4400 patients) that suggests an association between i.v. iron and an increased risk of infection (risk ratio 1.33; 95% confidence interval 1.10 --1.64) [95]. However, the authors of this analysis mentioned themselves that their finding might also be a false positive result since infection is generally not a predefined end point and missing data could have created a bias in the analysis.…”
Section: Safety and Tolerabilitymentioning
confidence: 45%
“…iron increases the risk of infections. However, relevant clinical evidence is sparse and inconclusive [81,95,96]. A large multicenter safety study that evaluated an iron status correction and a maintenance IS dosing regimen in 665 hemodialysis patients (covering 8583 doses of 100 mg iron) reported lower rates of infection-related hospitalizations (relative risk 0.54, p < 0.001) and mortality (relative risk 0.61, p = 0.08) compared with a historical general hemodialysis population [81].…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…Finally, a concern has been expressed in published studies of a potential negative impact on the occurrence of infection in vulnerable patients when treated with IV iron. Litton et al [21], in their systematic review and metaanalysis of randomized control clinical trials assessing the safety and efficacy of IV iron, found IV iron significantly increased the mean hemoglobin level and decreased the proportion of patients receiving RBC transfusions. They also found that IV iron therapy was associated with a significant increase in the risk of infection (relative risk, 1.33; 95% CI, 1.10-1.64).…”
Section: Discussionmentioning
confidence: 99%